Experimental Studies on the Benification of Fine Solids by Forth Flotation - Yousif Abdul-ahad, Muna (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
In this paper, the experiments were carried out in laboratory flotation cell treating solid fines. The effect of variables such as collector oil dosage, pine oil dosage and solid content of the feed slurry have been investigated on the flotation characteristics of low rank coal. Attempts have also been made to develop some empirical Eq. to predict the yield and ash content of concentrate with the operating variables, solids concentration, collector oil dosage, and pine oil dosage, to estimate the recovery at any operating conditions. The calculated results obtained from regression equation by correlating the variables with the yield and ash content of concentrate have been compared to study whether calculated values match closely with the experimental values by using F test at any level of significance.